Swift heavy ion induced formation of Al/polymer composite layer for low thermal emissivity in the IR range - Babrekar, Harshada A.; Jog, Jyoti Prakash; Mathe, Vikas L.; Avasthi, D. K.; Ojha, S.; Bhoraskar, S. V. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2012)
Composites of polymers with aluminium were formed by swift high energy ions of 150 MeV, which are used as low thermal emissivity materials for infrared wavelengths between 8-14 mu m. Emissivity and dielectric constants were studied for these structures. A semi-empirical model has been established to obtain the relation between emissivity and dielectric constant. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: composites; dielectric constant; Swift heavy ion; Thermal emissivity

Single step, phase controlled, large scale synthesis of ferrimagnetic iron oxide polymorph nanoparticles by thermal plasma route and their rheological properties - Raut, Suyog A.; Mutadak, Pallavi R.; Kumar, Shiv; Kanhe, Nilesh S.; Huprikar, Sameer; Pol, Harshawardhan V.; Phase, Deodatta M.; Bhoraskar, Sudha V.; Mathe, Vikas L. (Journal of Magnetism and Magnetic Materials, 2018)
In this paper we report single step large scale synthesis of highly crystalline iron oxide nanoparticles viz. magnetite (Fe3O4) and maghemite (gamma-Fe2O3) via gas phase condensation process, where micron sized iron metal powder was used as a precursor. Selective phases of iron oxide were obtained by variation of gas flow rate of oxygen and hence partial pressure of oxygen inside the plasma reactor. Most of the particles were found to possesses average crystallite size of about 20-30 nm. The DC magnetization curves recorded indicate almost super-paramagnetic nature of the iron oxide magnetic nanoparticles. Further, iron oxide nanoparticles were analyzed using Raman spectroscopy, X-ray photoelectron spectroscopy and Mossbauer spectroscopy. In order to explore the feasibility of these nanoparticles for magnetic damper application, rheological studies have been carried out and compared with commercially available Carbonyl Iron (CI) particles. The nanoparticles obtained by thermal plasma route show improved dispersion which is useful for rheological applications. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Iron oxide; magnetic properties; Nano-crystalline materials; Rheological properties; Thermal plasma